Post-stroke emotional incontinence or bipolar disorder? - Mnif L; Sellami R; Masmoudi J (Neuropsychiatric Disease and Treatment)
Leila Mnif,1 Rim Sellami,2 Jawaher Masmoudi2 1Department of Psychiatry “D”, Razi University hospital, Tunis, 2Department of Psychiatry “A”, Hédi Chaker University Hospital, Sfax, Tunisia Introduction: Post-stroke emotional incontinence and bipolar disorder are two disorders that involve the dysfunction of brain structures responsible for emotional regulation. The objective of this work is to study the links between these disorders through a clinical case. Case report: We present the case of a 43-year-old man without previous psychiatric history who experienced emotional incontinence after cerebrovascular events. He reacted promptly to selective serotonin reuptake inhibitor treatment. However, he experienced his first episode of hypomania after 6 months of antidepressant therapy. Adjunctive therapy with valproic acid and low-dose paroxetine was eventually added, resulting in complete improvement of both emotional incontinence and hypomania after 4 additional months of treatment. Conclusion: The clinician should carefully explore any history of premorbid bipolar disorder, personality disorder characterized by mood instability, and family history of bipolar disorder. Keywords: stroke, emotional incontinence, bipolar disorderA Letter to the Editor has been received and published for this article.